Polyphonic Thinking and the Divine. - Kanaris, Jim (Value inquiry book series., 2013)
Philosophy of religion is a highly diversified field. An apt description of it is "zoo." It conjures imagery of a species-wide cacophony of sights and sounds. While some bemoan what this description implies, contributors to this volume appreciate it. There is no reason why a zoo should intimate a den of confusion rather than an important condition of emergence and novelty. "Polyphonic" is the catchall term to capture this sentiment. It signals a way of thinking that resists the desire to siphon insight into manageable packets of information in the name of historicality and finitude. A polyphon.